Natural and Social Sciences Project Learning E-Module to Improve Science Process Skills in Aspects of Substances and Their Changes in Vocational Schools - Heni Nuraeni; Leny Helyawati; Indarini Dwi Pursitasari (Yayasan Keluarga Guru Mandiri, 2023)
Electronic modules are one solution to help students master and apply Science Process Skills in terms of creative economic and social aspects of substances and their changes. This research aims to provide a bibliometric literature review regarding developing the Natural and Social Sciences Project e-module. Articles were found using Publishing or Perish (PoP) software with the Google Scholar database. 67 out of 80 articles found in the Google Scholar database from 2015 to 2022 were analyzed in this research. Selected references are then managed using reference management software, namely Mendeley. After managing the database, this research classifies and visualizes it using VOSviewer software. This review provides an appropriate reference point for further research on the ‘IPA E-module’. The research conclusion is that online tutorials are more effective than non-online for teaching science process skills to students. Through the Natural and Social Sciences Project e-module, which is practical and valid, the science process skills of vocational school students increase.